Determinan keikutsertaan penapisan kanker serviks pada wanita pekerja seks - Ana Kurniati; Supriadi Gandamihardja; Mamun Sutisna (Jurnal Kesehatan Ibu dan Anak, 2013)
Cervical cancer is the second women killer in the world includes Indonesia. The number of cases of cervical cancer increased in city of Yogyakarta. Screening programs have not rum optimally so that the screening coverage is low and often the patients come in the last stage. Female sex workers (FSW) are one of the groups who are most vulnerable and at high risk of cervical cancer as well as a reservoir of HPV. The participant of FSW in cervical cancer screening is still low. This study aimed to analyze the determinant associated with female sex workers participation in cervical cancer screening. The design of this study was an observational study using correlative analysis. The subject was FSW who practice in Komplek Pasar Kembang Yogyakarta. Univariable analysis performed with the frequency distribution, bivariable analysis with Chi-square and multivariable analysis with logistic regression with significantly p-value <0.05. the result analysis using Chi-square showed that age was associated with cervical cancer screening participation (p =0,006) education was not associated with cervical cancer screening respondent had primary education, duration of work as FSW was associated with cervical cancer screening participation (p=0.000), knowledge was associated with participation in cervical cancer screening(p=0.010) and 40% of respondent knowledgeable were low, attitude was not related to participation in cervical cancer screening (p=0.164) and 47% of respondent had negative attitude. The result simultaneous analysis showed that knowledge was the most dominant determinant with the prevalence ratio was 3.67 (p< 0.05). this study suggests that sociodemographic (age and duration work as FSW) and knowledge were significantly associated with the participation in cervical cancer screening.